MTHFR C677T polymorphism as a risk factor of neural tube defects in Malay_a case control study - Hayati, AR; Zainal, AI; Tan, G.C; Ong, L.C; Khoo, T.B (Med J Malaysia, 2008)
Major congenital malformations occur in about 3% of newborn. Several studies have suggested that homozygosity for the C677T methylenetetrahydrofolate reductase (MTHFR) variant is a potential risk factor for neural tube defects (NTDs). It has been hypothesized that the maternal folic acid supplementation prevents NTDs by partially correcting reduced MTHFR activity associated with the variant form of the enzyme. This association has not been found in some ethnic groups. In this study, we attempted to assess the association between NTDs and MTHFR C677T in Malaysian Malay population. Results show that MTHFR 677TT genotype was absent in both patient and control groups.